Chapter 1: Fundamentals of Pharmacy Practice (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
AuthorDr. Amit Kumar, Associate Professor, Department of Pharmacy Practice, Amity Institute of Pharmacy, Amity University, Lucknow, IndiaAbstractPharmacy practice operates at the intersection of healthcare delivery, legal compliance, and ethical decision-making. Professional ethics in pharmacy establishes core values including beneficence, non-maleficence, autonomy, and justice, guiding pharmacists through moral dilemmas in patient care and business operations. Pharmacy laws create a regulatory framework spanning controlled substances management, dispensing requirements, and practice standards, with federal statutes like the Controlled Substances Act working alongside state-specific regulations that define scope of practice. Contemporary healthcare systems position pharmacists as medication experts within interdisciplinary teams, with roles expanding beyond traditional dispensing to include medication therapy management, immunizations, and direct patient care services in various practice settings. Effective communication serves as the foundation for patient-centered care, with pharmacists employing active listening, cultural sensitivity, and health literacy assessment to convey complex medication information, conduct motivational interviewing, and navigate challenging interactions with both patients and healthcare colleagues. These elements create the system within which pharmacy professionals deliver patient care, maintain legal compliance, and uphold the profession's commitment to public healthKeywords: Professional Responsibility; Medication Safety; Scope of Practice; Patient-Centered Care; Healthcare CollaborationVIEW PDF